Factors associated with work performance among the health personnel of Hospital Materno Infantil Carlos Showing Ferrari, Huánuco, 2022 - Aguilar Guerrero, Julio Fredy (2024)
Objective: To determine the factors associated with work performance among the health personnel of Hospital Materno Infantil Carlos Showing Ferrari, Huánuco, in 2022. Materials and methods: An observational, correlational and prospective study with a population of 146 health professionals and a sample size of 86 individuals. The information was collected through a questionnaire, where the variable work performance was evaluated with the Individual Work Performance Questionnaire by Koopmans et al. and validated with Cronbach’s Alpha greater than 0.8. The factors analyzed encompassed sociodemographic, work-related and academic variables. The statistical analysis was conducted using the chi-square test and the data were analyzed with IBM SPSS Statistics V25. Results: Most health professionals showed a very high-level work performance (60.47 %). Inferentially, sociodemographic factors such as age 31 to 45 years (p = 0.027) and 46 to 60 years (p = 0.045) were significantly associated with a very high-level work performance. Concerning work-related factors, work time greater than and equal to 21 years (p = 0.049) was the only factor significantly associated with a very high-level work performance. There was no association between academic factors and a very high-level work performance (p > 0.05). Conclusions: The factors significantly associated with a very high-level work performance among the health personnel were age 31 to 45 years and 46 to 60 years and work time greater than and equal to 21 years.